Review of the Refeeding Syndrome - Btaiche, Imad F. (2005)
Refeeding syndrome describes a constellation of metabolic disturbances that occur as a result of reinstitution of nutrition to patients who are starved or severely malnourished. Patients can develop fluid and electrolyte disorders, especially hypophosphatemia, along with neurologic, pulmonary, cardiac, neuromuscular, and hematologic complications. We reviewed literature on refeeding syndrome and the associated electrolyte abnormalities, fluid disturbances, and associated complications. In addition to assessing scientific literature, we also considered clinical experience and judgment in developing recommendations for prevention and treatment of refeeding syndrome. The most important steps are to identify patients at risk for developing refeeding syndrome, institute nutrition support cautiously, and correct and supplement electrolyte and vitamin deficiencies to avoid refeeding syndrome. We provide suggestions for the prevention of refeeding syndrome and suggestions for treatment of electrolyte disturbances and complications in patients who develop refeeding syndrome, according to evidence in the literature, the pathophysiology of refeeding syndrome, and clinical experience and judgment.